Gagasan Mistik Kiai Haji Achmad Siddiq: Menguak Ide tentang Moderasi Tasawuf: The Mystical Thought of Kiai Haji Achmad Siddiq: Unveiling the Idea of Sufi Moderation - Syamsun Ni'am (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2003)
The phenomenon of spiritual poverty in materialistic modern society has triggered a spiritual crisis and a need for a more moderate and inclusive religious approach. This article examines the mystical thought of KH. Achmad Shiddiq, a traditional cleric whose ideas on the modernization of Sufism are considered progressive. This study aims to reveal four main aspects of his thought: the historical aspect of Sufism, the principle of balancing the worldly and otherworldly, the concept of the Dzikrul Ghafilin litany as an effort to reform the tarekat (Sufi order), and the modernization of Sufism. Using qualitative library research with content analysis and reflective approaches, primary and secondary data from Shiddiq’s works and lectures were analyzed descriptively and comparatively. The findings show that Shiddiq viewed Sufism as ihsan (spiritual excellence) rooted in the Qur’an and Hadith. He introduced social worship to balance otherworldly and worldly orientations. Dzikrul Ghafilin was initiated as an alternative to tarekat without cultic devotion to a master, though in practice it has not entirely avoided similar patterns. His Sufi modernization emphasizes a pluralistic, inclusive, and humanistic approach to respond to modern life. In conclusion, Shiddiq’s thoughts are relevant for developing adaptive Sufism without losing its spiritual essence. It is recommended that these ideas be integrated into contemporary Islamic education and preaching. Fenomena kemiskinan batin di tengah masyarakat modern yang materialistik telah memicu krisis spiritual dan kebutuhan akan pendekatan keagamaan yang lebih sejuk dan inklusif. Artikel ini mengkaji pemikiran mistik KH. Achmad Shiddiq, seorang ulama tradisional yang gagasannya tentang modernisasi tasawuf dinilai progresif. Penelitian ini bertujuan untuk mengungkap empat aspek utama pemikirannya: aspek kesejarahan tasawuf, prinsip keseimbangan duniawi-ukhrawi, konsep wirid Dzikrul Ghafilin sebagai upaya pembaruan tarekat, serta modernisasi tasawuf. Melalui metode penelitian kualitatif berbasis kajian pustaka dengan analisis isi dan pendekatan reflektif, data primer dan sekunder dari karya serta ceramah Kyai Achmad dianalisis secara deskriptif-komparatif. Hasil penelitian menunjukkan bahwa Kyai Achmad memandang tasawuf sebagai ihsan yang berlandaskan Al-Qur’an dan Hadis. Ia memperkenalkan ibadah sosial untuk menyeimbangkan orientasi akhirat dan dunia. Wirid Dzikrul Ghafilin dirintis sebagai alternatif tarekat tanpa kultus terhadap mursyid, meskipun dalam praktiknya belum sepenuhnya berhasil menghindari pola serupa. Modernisasi tasawuf yang digagasnya menekankan pendekatan sufistik yang pluralis, inklusif, dan humanis untuk merespons kehidupan modern. Kesimpulannya, pemikiran Kyai Achmad relevan untuk mengembangkan tasawuf yang adaptif tanpa kehilangan esensi spiritual. Rekomendasinya, gagasan ini perlu diintegrasikan dalam pendidikan pesantren dan dakwah kontemporer.